2008
DOI: 10.2337/dc07-2306
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin and Progression of Diabetic Nephropathy in Patients With Type 1 Diabetes

Abstract: OBJECTIVE -The purpose of this study was to elucidate whether serum adiponectin is associated with progression of diabetic nephropathy in type 1 diabetic patients.RESEARCH DESIGN AND METHODS -This was a prospective follow-up study as a part of the nationwide Finnish Diabetic Nephropathy Study; 1,330 type 1 diabetic patients were followed for 5.0 Ϯ 2.2 years. Patients were divided at baseline into three groups according to their urinary albumin excretion rate (AER) in three consecutive overnight or 24-h urine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 23 publications
4
57
0
4
Order By: Relevance
“…Indeed, it has been debated whether the use of AICAR could be compromised in patients with diabetic nephropathy because research indicates that the drug may increase adiponectin [13]. Although adiponectin is generally described as a protective adipokine [16] and thought to protect podocyte function in early onset kidney disease [18,[42][43][44], the role of adiponectin in the later stages of human renal failure is unclear [18] with some studies suggesting that it is harmful [19,20]. Thus, our finding that AICAR attenuated HFD-induced kidney disease in an adiponectin-independent manner may indicate that the drug is a more suitable therapeutic agent for patients with advanced nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been debated whether the use of AICAR could be compromised in patients with diabetic nephropathy because research indicates that the drug may increase adiponectin [13]. Although adiponectin is generally described as a protective adipokine [16] and thought to protect podocyte function in early onset kidney disease [18,[42][43][44], the role of adiponectin in the later stages of human renal failure is unclear [18] with some studies suggesting that it is harmful [19,20]. Thus, our finding that AICAR attenuated HFD-induced kidney disease in an adiponectin-independent manner may indicate that the drug is a more suitable therapeutic agent for patients with advanced nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Although adiponectin is generally described as a protective adipokine [16], several clinical studies have reported a paradoxical inverse association between circulating adiponectin levels and renal function [17,18]. Specifically, increased adiponectin levels correlate with diabetic nephropathy [19,20], advanced chronic kidney disease (CKD) [21][22][23] and increased risk of mortality [24]. As we cannot exclude the compromising role of adiponectin in CKD patient groups, it is critical to assess if AICAR-mediated actions are adiponectin dependent to determine its suitability as a drug to target obesity-related pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon these well established associations, one would expect an inverse relationship between circulating adiponectin and albuminuria. However, several studies have described a 'paradoxical' elevation of serum adiponectin concentrations in patients with elevated UAE [12][13][14][15][16][17][18]. The reasons for such unexpected findings are unknown.…”
Section: Introductionmentioning
confidence: 90%
“…Most [12][13][14][15][16][17][18], although not all [38][39][40] previous studies have reported a direct correlation between circulating adiponectin and UAE rate. This finding was somewhat 'unexpected' if insulin resistance was regarded as the common soil of both variables, and pointed to the role of confounding factors, including diabetes, kidney disease and related treatments, possibly affecting previous studies [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the assistance of the FinnDiane Study Group [13] and, especially, the skilled technical assistance of S. Lindh and A. Sandelin. SNP genotyping based on Sequenom technology was performed at the Finnish Genome Center.…”
Section: Acknowledgementsmentioning
confidence: 99%